Bacterial functional redundancy along a soil reclamation gradient - Yin, B.; Crowley, D.; Sparovek, G.; De Melo, W. J.; Borneman, J. (Amer Soc Microbiology, 2000)
A strategy to measure bacterial functional redundancy was developed and tested with soils collected along a soil reclamation gradient by determining the richness and diversity of bacterial groups capable of in situ growth on selected carbon substrates. Soil cores were collected from four sites along a transect from the Jamari tin mine site in the Jamari National Forest, Rondonia, RO, Brazil: denuded mine spoil, soil from below the canopy of invading pioneer trees, revegetated soil under new growth on the forest edge, and the forest floor of an adjacent preserved forest. Bacterial population responses were analyzed by amending these soil samples with individual carbon substrates in the presence of bromodeoxyuridine (BrdU), BrdU-labeled DNA was then subjected to a 16S-23S rRNA intergenic analysis to depict the actively growing bacteria from each site, the number and diversity of bacterial groups responding to four carbon substrates (L-serine, L-threonine, sodium citrate, and or-lactose hydrate) increased along the reclamation-vegetation gradient such that the preserved forest soil samples contained the highest functional redundancy for each substrate. These data suggest that bacterial functional redundancy increases in relation to the regrowth of plant communities and may therefore represent an important aspect of the restoration of soil biological functionality to reclaimed mine spoils. They also suggest that bacterial functional redundancy may be a useful indicator of soil quality and ecosystem functioning.